(untitled) (Academic Journal of International University of Erbil, 2026)
The CACNA1C gene affects calcium flow in heart and vessel cells, variants in this gene can alter calcium handling, influencing vascular tone and cardiac contractility, thereby contributing to the development and progression of hypertension. This study aims to evaluate the variation in serum levels of creatine kinase-MB(CK-MB), myoglobin, and cardiac troponin I among hypertensive patients, and to determine whether these levels show a marked difference among individuals receiving antihypertensive therapy in hypertensive patients and untreated healthy controls. It also examines CACNA1C gene variation between HTN patients and healthy explore its potential role in hypertension and cardiac biomarker levels. The study utilized a cross-sectional design and was conducted at Shahid Dr. Khalid Teaching Hospital in Koya, Erbil. A total of 75 participants were enrolled, including 55 individuals diagnosed with hypertension and 20 healthy controls. The investigation involved measuring cardiac biomarkers such as Troponin I, CK-MB, and Myoglobin. Additionally, PCR amplification of the CACNA1C gene was carried out using DNA extracted from blood samples, prepared with the Beta Bayern Tissue and Blood DNA Preparation Kit, at the research center of Erbil International University. The analysis between groups and diabetes duration was performed through GraphPad Prism 10. The results showed non-significant difference in troponin I level between the CCB and ARB groups. A significant reduction in myoglobin level was observed in the ARB group compared to the CCB group. Nevertheless, there were non-significant differences between the control group and either the CCB or ARB groups. There were non-significant differences in CK-MB level between any of the groups. This suggests that CK-MB concentrations remained similar regardless of treatment groups. Additionally, genetic result the control group showed no variation in rs1051375 (all G/G), whereas both the CCB and ARB patient groups exhibited SNP variation, including G/A and A/A genotypes. This finding indicates a potential link between the polymorphism and hypertension or its treatment response. The CACNA1C rs1051375 genotype distribution differed between controls and hypertensive patients, with a shift toward the A allele, especially in those on CCBs. ARB treatment showed greater reduction in myoglobin levels, suggesting better cardio protection. These findings support the role of genetic markers and biomarkers in guiding personalized hypertension therapy.